PROCESS AND SYSTEMS 'Fast-track' pathway for resectable pancreatic cancer: barriers and facilitators to implementation across a regional network. Issue 3 (2021) - Yannoulias, Basil; Exworthy, Mark; Roberts, Keith J
No abstract available